2012
DOI: 10.1088/0022-3727/45/43/435203
|View full text |Cite
|
Sign up to set email alerts
|

Cathode diameter and operating parameter effects on hafnium cathode evaporation for oxygen plasma cutting arc

Abstract: Abstract. The effects of cathode holder shape on a plasma cutting arc are investigated using a 2-D thermofluid model developed for arc plasma with consideration of hafnium cathode evaporation. The cathode holder shape is defined a convex structure which protrudes from the surface of the cathode holder. Results show that the gas flow near the hafnium cathode is attracted towards to cathode with effect of convex cathode holder. The temperature of cathode surface decreases markedly with the higher protrusion of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…Further development of diagnostic methods applicable to non-equilibrium regions of the plasma is also required, for example, the 2D timedependent laser-scattering techniques that have been applied to combustion and circuit breaker arcs. Development of methods that allow access to regions that are hidden from view, such as within plasma spraying and cutting torches [128,132], within the kerf in plasma cutting [128,131], and beneath the flux in submerged arc welding [127], would greatly increase our understanding of these approaches. Figure 25 shows two innovative approaches.…”
Section: Advances In Science and Technology To Meet Challengesmentioning
confidence: 99%
“…Further development of diagnostic methods applicable to non-equilibrium regions of the plasma is also required, for example, the 2D timedependent laser-scattering techniques that have been applied to combustion and circuit breaker arcs. Development of methods that allow access to regions that are hidden from view, such as within plasma spraying and cutting torches [128,132], within the kerf in plasma cutting [128,131], and beneath the flux in submerged arc welding [127], would greatly increase our understanding of these approaches. Figure 25 shows two innovative approaches.…”
Section: Advances In Science and Technology To Meet Challengesmentioning
confidence: 99%
“…Comparison of the obtained values with the available information on these parameters showed a reasonable agreement. Long et al (2012) studied the evaporation of a hafnium cathode in a plasma cutting arc torch. The total amount of mass loss due to hafnium cathode evaporation was predicted to be enhanced with increasing gas flow rate, gas pressure, and cathode diameter as well.…”
Section: Button-type Cathodes For Oxidizing Gasesmentioning
confidence: 99%
“…In addition, multiple reports of studies investigating the process parameters related to plasma arc cutting have been published [9]- [14]. Nemchinsky [9] confirmed that swirling the gas enhances the axial gas flow from the cathode.…”
Section: Introductionmentioning
confidence: 97%
“…The probability of the evaporated atom/ion returning to the cathode is increased by the slowing down of the gas flow near the cathode and thus decreases the net erosion rate. On the other hand, our previous works [13,14] have already used a numerical model for a fundamental study of the effect of various swirl gas angle and process parameters on behaviour of hafnium cathode evaporation in a plasma cutting arc torch. Results have shown that a larger swirl gas angle causes a high-temperature plasma area in front of the cathode surface shrunken in a radial direction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation